In utero exposure to alloantigens primes alloimmunization to platelet transfusion in mice. Issue 3 (18th December 2020) - Poston, Jacqueline N.; Jash, Arijita; Hannan, Lindsay M.; Hay, Ariel M.; Usaneerungrueng, Chomkan; Howie, Heather L.; Kapp, Linda M.; Zimring, James C.
Abstract: Background: Platelet transfusions remain a mainstay of treatment for many patients with thrombocytopenia, but can lead to alloantibodies to Human Leukocyte Antigens (anti‐HLA) resulting in inadequate responses to subsequent platelet transfusions (refractoriness), as well as complicate transplantation. Despite substantial decreases in alloimmunization with the implementation of leukoreduction, a significant percentage of patients still become alloimmunized following platelet transfusions. It remains unclear why some patients make anti‐HLA antibodies, but others do not make anti‐HLA antibodies even with chronic transfusion. Antecedent pregnancy correlates with risk of alloimmunization due to platelet transfusion in humans ‐ however, isolation of pregnancy as a single variable is not possible in human populations. Study Design and Methods: A tractable murine model of pregnancy and transfusion was engineered by breeding C57BL/6 (H‐2 b ) dames with BALB/c (H‐2 d ) sires. After pregnancy, female mice were transfused with leukoreduced platelets from F1 (H‐2 b/d ) donors that expressed the same paternal major histocompatibility complex (MHC) H‐2 d alloantigens as the sires. Control groups allowed isolation of pregnancy or transfusion alone as independent variables. Alloimmunization was determined by testing serum for antibodies to H‐2 d MHC alloantigens. Results: No alloantibodies were detected after pregnancy alone, or in response to transfusion of platelets alone; however, significant levels of alloantibodies were detected when pregnancy was followed by transfusion. Conclusions: These findings isolate antecedent pregnancy as a causal contribution to increased frequencies of alloimmunization by subsequent platelet transfusion in mice and provide a platform for ongoing mechanistic investigation.